Development of Science Learning Media Using Supcath Educational Games to Improve Student Learning Outcomes - Jamalludin Jamalludin; Sri Handono Budi Prastowo; Rif’ati Dina Handayani (Postgraduate, University of Mataram, 2023)
Technological developments have a rapid influence on the world of education so there is a need for innovation. The student’s ability to solve problems is still relatively low, especially in solid pressure material. This study aims to produce educational game-based learning media that is valid, effective, and able to improve student learning outcomes. The instructional media developed by this researcher specifically focus on material related to pressure for grade 8. This research is a Research and Development study with the ADDIE research design (Analysis, Design, Development, Implementation, and Evaluation). Data was collected using expert validation sheets, student test sheets, and student response sheets. The results showed that learning media was valid and effective with an average percentage of validator ratings of 92.6% and an average N-gain value of 0.6. Referring to the results of the analysis that has been carried out, this learning media can be concluded as the learning media that are valid, effective, and able to improve student learning outcomes.